Kemanfaatan, keadilan, dan kepastian hukum restorative justice pada ketentuan perpajakan - Hapsari, Sita Dewi (Directorate General of Taxes, 2024)
Restorative justice has been implemented in tax provisions, namely the KUP Law and the PPSP Law which regulate tax collection, audits and investigations. Restorative justice is further reaffirmed in the Law on Harmonization of Tax Regulations (UU HPP), which is known to be contained in the explanation of Article 40B clause (3), Article Article 44B clause 2a and Article 64 clause (2). It is estimated that tax law enforcement with a restorative justice approach can be a more comprehensive and sustainable solution in dealing with violations. Dispute resolution is focused on efforts to reconcile the parties, in this case between countries positioned as victims and parties who commit violations. This is done with the aim of creating a better climate of compliance and reducing protracted problems. This journal article was prepared in order to analyze the value of benefit, justice and legal certainty regarding the implementation of the article on restorative justice regulated in the UU HPP for violations that have the potential to harm the country's economy. By using non-doctrinal legal research methods based on theory and application to regulations, it is hoped that the results of theoretical analysis related to the principles of restorative justice can provide further insight into how the values of benefit, justice and legal certainty are applied as law enforcement, especially in the field of taxation.